2020
DOI: 10.1186/s43162-020-00021-0
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of kidney diseases in Northern India: an overview through histopathological findings in biopsy-proven cases

Abstract: Background A kidney biopsy is being increasingly performed for the diagnosis of renal diseases. It is a reasonably safe procedure that helps not only to reach the correct diagnosis based on histopathological findings but also helps in predicting the clinical course and outcome. The pattern of kidney diseases varies not only in far apart geographical regions but also in the same country. This study was done to evaluate the demographic pattern and spectrum of kidney diseases in renal biopsy-proven cases in an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…Furthermore, most of the transplant recipients were male, and all the transplanted kidneys were received from living donors, which was different from the present study (20). In Kuma's study, the average age was about 42 years, and female recipients were more than males (21). In the study by Alkindi et al, the average age of the recipients was about 44 years, most of the transplant recipients were men, and more than 70% of the transplanted kidneys were received from non-living donors (22).…”
Section: Discussioncontrasting
confidence: 83%
“…Furthermore, most of the transplant recipients were male, and all the transplanted kidneys were received from living donors, which was different from the present study (20). In Kuma's study, the average age was about 42 years, and female recipients were more than males (21). In the study by Alkindi et al, the average age of the recipients was about 44 years, most of the transplant recipients were men, and more than 70% of the transplanted kidneys were received from non-living donors (22).…”
Section: Discussioncontrasting
confidence: 83%
“…17 as those undergoing kidney biopsies for any indications, in countries such as India, Nepal, Korea, Japan, and Belgium. 7,8,18,19 MCD/IgMN was the most observed pathologic pattern in patients presenting with NS, except in the UVH practice, where FSGS was the predominant finding. The registry conducted at one of the largest university-based hospitals in Thailand, involving 3275 kidney biopsies, revealed that IgMN accounted for most primary glomerulopathy diagnoses (n = 986, 46%).…”
Section: Final Diagnoses By Kidney Biopsy Indicationsmentioning
confidence: 87%
“…As a result, they tend to allocate their limited resources towards diagnosing patients with advanced diseases, necessitating more judicious utilization of diagnostic procedures. IgAN emerges as the most prevalent pathological diagnosis in patients presenting with asymptomatic urinary abnormalities, as well as those undergoing kidney biopsies for any indications, in countries such as India, Nepal, Korea, Japan, and Belgium 7,8,18,19 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations